ANALYSIS OF GENETIC DIVERSITY OF SOME OLIVEGENOTYPES USING RANDOM AMPLIFIED POLYMORPHIC DNA (RAPD) MARKERS - Asmaa A. Al-Obeide; Akeel H. Al-Assie (Tikrit Journal of Pure Science)
This study aimed to use the Random Amplified Polymorphic DNA (RAPD) markers based on the PCR technique in the analysis of genetic variation among seven olive grown cultivar Olea europaea L. cultivars in Saladin province in Iraq Eighteen primers were used in RAPD reactions ,Results of RAPD experiments showed different loci of the bands. The total number of loci defined by the primer was 99 loci, of which 18 were general sites for all samples and 81 different locations. (OPP-01, OPM-15, OPK-13,1700bp) highest, and the lowest partial size in the primers [100 bpOPH-14, OPG-05] The variance between the samples studied was highest, as OPZ-08 (9.0), and less than in OPM-03 (2.1) The ability to discriminate for the primers was characterized by the OPZ-08 primer with a maximum discriminating higher of 9.0. The OPM-03 primer was characterized by the least discriminating of 2.1A total of 429 total bands bundles were produced, of which 18 were general main bands and 411 were polymorphic bands, The total number of distinctive bands resulting from in this study was 49. 21 absent band and( 28) Unique bands. The sample Santacatrina 5 received the highest number of missing bands, reaching (16 bands) Shamlaily is a sample 2 with the highest number of unique bands 7. The genetic distance values ​​ranged from (0.769-0.089), the lowest value of the genetic distance (0.089) and the difference between the four types (Frantoryo and 3 photo), and the highest genetic distance was between 5 (Santacaterina and 6) 0.769.While the analysis of the genetic relationship revealed that there are three main groups, including the first sample (5) Santacaterina, the second group including subgroups B1, B2 included the first B1 sample only one sample Krodsoo, while the second group B2 has included the remaining items Shamali, Sorani, Frantoyo Duhkan, Qaisi